Influence E-Service Quality Towards Customer Retention and Word of Mouth (WOM) Mediated By Customer Satisfaction - Mei Yasfi, Syalsabila; Pardede, Ratlan (Jurnal Indonesia Sosial Sains, 2023)
This study aims to investigate various significant relationships in the context of the online retail industry. The focus includes analyzing the positive influence of E-Service Quality on Customer Retention, Customer Satisfaction, and Word of Mouth, as well as identifying the positive influence of E-Service Quality on Customer Satisfaction. Furthermore, this study looked for the positive influence of Customer Satisfaction on Customer Retention and Word of Mouth. In addition, the study will also consider the effect of E-Service Quality on Customer Retention and Word of Mouth by mediating through Customer Satisfaction. This study used quantitative methods with survey techniques using questionnaires. The research sample was 190 respondents domiciled in Jabodetabek. The research instrument is prepared based on the operationalization of variables measured using the Likert scale. This research concludes that E-Service Quality plays an important role in influencing Customer Retention, Customer Satisfaction, and Word of Mouth in the context of the online retail industry. The quality of electronic services has a positive and significant impact on customer retention, retaining customers, and influencing their satisfaction. In addition, the quality of electronic services also plays a role in the development of brand reputation through positive recommendations and word-of-mouth influence. The results also show that Customer Satisfaction has a central role in linking the quality of electronic services with Customer Retention and Word of Mouth